2019
DOI: 10.1097/cm9.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complexity and prognostic outcome of small volume renal cell carcinoma with high-level venous tumor thrombus and large volume renal cell carcinoma with low-level thrombus

Abstract: Background:Radical nephrectomy with thrombectomy is one of the most difficult and complicated urological operations. But the roles of renal tumor volume and thrombus level in surgical complexity and prognostic outcome are not clear. This study aimed to evaluate the surgical complexity and prognostic outcome between the volume of renal cell carcinoma (RCC) and the level of venous tumor thrombus.Methods:The clinical data of 67 RCC cases with renal vein or inferior vena cava (IVC) tumor thrombus from January 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…The latest version introduces nearly 1000 enhancements and bug xes for better performance and stability. This software has been used and cited in more than 443 publications and more than 36 pulmonary-speci c articles 14 . And to the best of our knowledge, the present study is the rst to perform a 3D volume measurement for patients with inferior vena cava tumor thrombus in locally advanced renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The latest version introduces nearly 1000 enhancements and bug xes for better performance and stability. This software has been used and cited in more than 443 publications and more than 36 pulmonary-speci c articles 14 . And to the best of our knowledge, the present study is the rst to perform a 3D volume measurement for patients with inferior vena cava tumor thrombus in locally advanced renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] In light of the potential for major intra-operative complications, it is essential that more accurate pre-operative predictive models for megascopic invasion of the IVC wall requiring IVC resection are established to help surgeons overcome the challenges and select the best treatment strategies. [ 17 ] In this context, in the present study, imaging features of the VTT at the RVo and IVC were identified and measured by pre-operative imaging, and the features were used to predict whether IVC needed to be performed at the time of tumor thrombectomy for patients with a level I–IV thrombus. Specifically, an AP diameter of the VTT at the RVo of >17.0 mm and the presence of complete occlusion of the IVC were independently associated with a higher probability of IVC resection.…”
Section: Discussionmentioning
confidence: 99%
“…4) Patients with right adrenal metastasis or tumor invasion underwent ipsilateral adrenalectomy. The operative procedures for the different tumor thrombus levels were as follows [10]: For Mayo level I, the IVC was exposed and partially occluded using Satinsky forceps. For Mayo level II, the distal end and proximal end of the IVC and the contralateral renal vein were exposed and occluded in sequence.…”
Section: Operative Methodsmentioning
confidence: 99%